SOSIALISASI PEMASARAN ONLINE DENGAN PEMANFAATAN TEKNOLOGI INFORMASI KELOMPOK PEDAGANG ITC BSD LT UG TANGERANG SELATAN - Eka Cahyaningrum; Nadia Supriyani; Perdana Sendy Wahyu Lamantara; Muhammad Reynaldi Mahendra; Bagus Adhi Karyono; Raka Shotta Altafyanto; Ridlo Sahrum Azamzami (AMMA : Jurnal Pengabdian Masyarakat, 2022)
This service activity aims to empower merchant groups at ITC BSD included in the category of Micro, Small and Medium Enterprises (MSMEs) by providing counseling about online marketing so that they can expand the marketing reach of the products they produce. The purpose of service activities is achieved by conducting counseling to the target audience - through delivery materials related to online marketing to provide insight into the use of electronic media or the internet for support their marketing activities. The target audience is traders who are in ITC BSD. Opening the insight of the target audience so that they have the ability to market the product generated online through the use or utilization of electronic media or the internet so that they can reach a wider market at low cost..